2-Phenylpyridine-based phosphorescent Ir(III) complexes for highly efficient greenish-blue organic light-emitting diodes with EQEs up to 33.5%. (February 2023) - Lan, Ying; Liu, Di; Li, Jiuyan; Wan, Huihui; Mei, Yongqiang
Abstract: A group of heteroleptic cyclometalated iridium complexes Ir1–Ir4 were designed with 2-phenylpyridine (ppy) derivatives as cyclometalating ligands and 2-(3-(trifluoromethyl)-1 H -pyrazol-5-yl)pyridine (fppz) or 2-(5-(4-(trifluoromethyl)phenyl)-2 H -1, 2, 4-triazol-3-yl)pyridine (Htaz) as ancillary ligands. The incorporation of electro-donating group into ppy ligands to elevate ligands-centered 3 π-π* energy level and utilization of fppz or Htaz ancillary ligands combined to tune the intrinsic electronic properties. These complexes showed greenish-blue or green phosphorescence and are characterized by high photoluminescence quantum yields of up to 70% and short lifetimes below 1 μs. The organic light-emitting diodes (OLEDs) with Ir1–Ir4 as doped emitters all exhibited high efficiencies with low efficiency roll-off. Particularly, the Ir3 device exhibited distinguished performances with the maximum current efficiency of 86.9 cd A −1 and an external quantum efficiency (EQE) of 33.5%. Even at high brightness of 1000 cd m −2, the EQE still remained at 24.6%. Evidently the EQE of 33.5% of Ir3 device is one of the highest efficiencies ever reported for greenish-blue phosphorescence OLEDs. Graphical abstract: By selecting dimethylamino or ethoxyl decorated 2-phenylpyridine as cyclometalating ligands and fppz and Htaz as ancillary ligands, a group of heteroleptic iridium complexes were developed with characters of high photoluminescence quantum yields up to 70% and short lifetimes below 1 μs. All complexes exhibited good efficiencies over 20% in OLEDs, and the Ir3 device gave the highest EQEmax of 33.5% and low efficiency roll-off, being one of the highest EQEs for greenish-blue phosphorescence OLEDs so far. Image 1 Highlights: Highly efficient iridium complexes are developed with decorated phenylpyridine as cyclometalating ligands. Rich-nitrogen heterocyclic ligands were utilized as the ancillary ligands. These complexes are characterized by high PLQY, short excited state lifetimes below 1 μs, and high EQEs over 20% in OLEDs. The Ir3 based OLED gave a maximum EQE of 33.5%, being among the highest efficiencies for greenish-blue OLEDs so far. Fluorine-free feature of the cyclometalating ligands was attributed to be one reason for extra efficiency stability.